Epidemiology and aetiology of childhood ocular trauma in the Republic of Suriname. (24th March 2016) - Minderhoud, Janna; van Nispen, Ruth M. A.; Heijthuijsen, Astrid A. A. M.; Beunders, Victoria A. A.; Bueno de Mesquita‐Voigt, Anne‐Marie T.; Moll, Annette C.; Mans, Dennis R. A.; Saeed, Peerooz
Abstract: Purpose: To describe the epidemiology and aetiology of ocular trauma in school‐aged children who previously visited the Suriname Eye Centre (SEC) of the Academic Hospital Paramaribo. Methods: In a hospital‐based retrospective study, all cases of children who were school aged (8–15 years) at the time of the survey and previously underwent evaluation and/or treatment at the SEC because of ocular trauma were analysed. Demographic and ophthalmologic data were taken out of patient records; eye injuries were classified using the Birmingham Eye Trauma Terminology classification system. Main outcome measures were type of injury, mechanism/cause of injury, final visual acuity (VA), hospitalization, patient delay and patient compliance. Results: Five hundred and thirty‐eight records were analysed which included 35 open globe injuries (OGI) (7%), 458 closed globe injuries (85%), five orbital fractures (1%) and 40 eyelid injuries (7%). The most frequent causes of trauma represented body parts (18%) and sticks or branches (13%) and resulted from poking (20%) or punching (13%) the eye. Final VA < 6/60 was reported in 58% of registered OGI. Where living in rural areas (p = 0.007), OGI (p < 0.0001) and poor compliance to scheduled check‐ups (p < 0.0001) were statistically significantly related to an unfavourable outcome, patient delay was not. Patients having OGI were more often hospitalized than children with other injuries (p < 0.0001). Conclusion: This is the first study providing data on childhood ocular trauma in Suriname. As the majority of childhood injuries were avoidable, new policies should aim at developing effective, targeted preventive strategies to promote awareness, parental supervision, immediate action and compliance.